Evaluation of a six‐dye multiplex composed of 27 markers for forensic analysis and databasing. Issue 9 (16th July 2020) - Wang, Shuangshuang; Song, Feng; Xie, Mingkun; Zhang, Ke; Xie, Bowen; Huang, Zhanglong; Luo, Haibo
Abstract: Background: Short tandem repeat (STR) markers play a significant role in genetic applications and have proved to be effective for the personal identification in forensic medicine. In this study, a six‐dye multiplex composed of 23 autosomal STR loci ( TH01, D3S1358, Penta D, D6S1043, D21S11, TPOX, D1S1656, D12S391, Penta E, D10S1248, D22S1045, D19S433, D8S1179, D2S1338, D2S441, D18S51, vWA, FGA, D16S539, CSF1PO, D13S317, D5S818, D7S820 ), one Y chromosome STR ( DYS391 ), two internal quality control markers (Quality Sensor QS1 and QS2), and Amelogenin was evaluated. Methods: Evaluation studies, including PCR‐based studies, sensitivity studies, species specificity studies, stability studies, DNA mixture studies, concordance studies, and precision evaluations were performed according to the guidelines of "Validation Guidelines for Forensic DNA Analysis Methods (2016)" by the Scientific Working Group on DNA Analysis Methods (SWGDAM). In addition, the forensic characteristics of 357 unrelated male samples from Han and Hui populations in China were investigated using 27 markers. Results: Full STR profiles were obtained from different reaction volumes (5 25 μl), cycle numbers (28 34 cycles) and annealing temperatures (58 62°C). All STR profiles were obtained at humic acid concentration of up to 200 ng/μl and hematin concentration of up to 500 μM. No peaks were observed in most common animal samples except two innovative internal PCR controls (Quality Sensor QS1 and QS2). The six‐dye multiplex showed a notably high value for the combined probability of exclusion (CPE), exhibiting values of with 0.99999999977688 in the Han population and 0.999999999583875 in the Hui population. The values of combined probability of discrimination (CPD) were 0.999999999999999999999999999997453 in the Han population and 0. 999999999999999999999999999994398 in the Hui population. In addition, concordance studies showed that there was no difference with the AGCU Express Marker 22 Kit. Conclusion: The results indicated that the Investigator ® 26plex QS Kit is a robust, reliable, and suitable tool for forensic analysis and databasing. Abstract : A 6‐dye multiplex composed of 27 markers were evaluated, according to SWGDAM guidelines. High power of discrimination and cumlative probability of paternity exculsion value in two Chinese population. The 6‐dye multiplex is robust, reliable and suitable tool for forensic analysis and data‐basing.